"Forewarned and forearmed": Long-term childhood cancer survivors' and parents' information needs and implications for survivorship models of care. Issue 2 (February 2017) - Vetsch, Janine; Fardell, Joanna E.; Wakefield, Claire E.; Signorelli, Christina; Michel, Gisela; McLoone, Jordana K.; Walwyn, Thomas; Tapp, Heather; Truscott, Jo; Cohn, Richard J.; ,
Highlights: 75% of participants had more than one unmet information need. Survivors had highest unmet information needs for late effects. Parents had highest unmet information needs for fertility issues. Unmet information needs were more pronounced for parents of survivors. Lower overall health and greater anxiety/depression were predictors of unmet needs. Abstract: Objective: This mixed-method study assessed 1) survivors' and parents' information needs; and 2) associations between unmet information needs and clinical and socio-demographic characteristics. Methods: Stage 1: CCS and parents of CCS, >5years post-diagnosis completed a questionnaire on information needs, overall health and perceived risk. Predictors for unmet information needs were assessed by multivariable regression. Stage 2: participants were interviewed in-depth on these topics. Results: Questionnaires were completed by 485 participants comprising 322 survivors (mean age: 26.7years, SD = 7.9; time since diagnosis: 19.7years, SD = 8.8) and 163 parents (child age: 12.9years, SD = 2.4; time since diagnosis: 9.7years, SD = 2.3), and complemented by 70 interviews. Survivors reported unmet information needs about late effects (57.5%) and parents for fertility issues (62.5%). Survivors had more unmet needs for medical information whereas parents had significantly more regarding sexual issues and lifestyle. Being a parent (p = 0.001), dissatisfaction with follow-up care (p = 0.003), lower overall health (p = 0.014), higher perceived risk of late effects (p < 0.001), and greater anxiety/depression (p < 0.001) were significantly associated with more unmet needs. Conclusion: Unmet information needs were common for survivors and parents of CCS. Practice implications: Future efforts towards tailoring information on potential late effects, healthy lifestyles and follow-up care may help to address unmet information needs.